Tinjauan Yuridis terhadap Hukum Bagi Pengguna Narkotika dalam UU No. 35 Tahun 2009 Melalui Penanganan Lembaga Bantuan Hukum - Siti Rohmah; Novita Alfa Ramadhan; Lucky Dafira Nugroho (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Drug abuse is a complex and evolving legal problem in Indonesia. Law Number 35 of 2009 concerning Narcotics strictly regulates provisions for drug users, both in terms of criminal penalties and rehabilitation. In practice, drug users are often treated as criminals and sentenced to imprisonment, although normatively the law also provides opportunities for rehabilitation as a form of protection and recovery. This study aims to examine the legal provisions for drug users from a legal perspective, analyze the role of Legal Aid Institutions (LBH) in handling drug abuse cases, and identify obstacles faced in implementing such legal assistance. The methods used are normative legal and sociological legal approaches, with data collection techniques through literature and documentation. The results of the study indicate that drug users should have access to rehabilitation, not just punishment. LBH plays a crucial role in providing legal assistance and advocating for the implementation of restorative justice. However, several obstacles remain, such as limited resources, a lack of understanding among law enforcement officials, and public stigma. Joint efforts are needed between the government, LBH, and the community to realize fair legal protection for drug users.